High-Frequency Ultrasound Imaging–Guided Wedge Resection: An Effective Treatment for Paraurethral Duct Dilatation Following Gonococcal Paraurethral Duct Infection in Men - Wenge Fan; Qingsong Zhang; Zhijiang Fan; Xun Ye; Tingwang Jiang (American Journal of Men's Health, 2018)
This study was performed to evaluate the therapeutic effects of wedge resection on male paraurethral duct dilatation following gonococcal paraurethral duct infection. Twenty-six men with paraurethral duct dilatation following gonococcal paraurethral duct infection were enrolled. Their lesions underwent wedge resection after examination using an ACUSON X300 ultrasound system. The anesthetic method, surgical duration, intraoperative blood loss, wound healing time, complications, sequelae, and curative effect were assessed. All 26 men received local infiltration anesthesia. The mean surgical duration was 18.65 ± 2.50 min (range, 14–23 min), the mean intraoperative blood loss was 10.50 ± 1.68 ml (range, 8–14 ml), and the mean wound healing time was 14.73 ± 1.31 days (range, 13–17 days). The lesions were cured in all patients (100%). The postoperative wounds healed in all patients. No complications or glans defects were observed in any patients. The study identifies that high-frequency ultrasound imaging–guided wedge resection is an effective and safe therapy for paraurethral duct dilatation following gonococcal paraurethral duct infection in men.